The strategy of internalizing the values of the characters in al-Mumtaz Islamic Boarding School - Iplih, Muhammad (ATTARBIYAH: Journal of Islamic Culture and Education, 2017)
AbstractCharacter is an action that is done without thinking and consideration first. So the person who is character is the person who performs and responds to something with spontaneous and reflexes. The formation of good character requires the right processes and strategies. Studies and research on character are increasingly important to do considering the recent phenomena are related to the deterioration of values and characters performed by children who are still relatively small and many other actions that deviate from the values of Islamic character that we can see every day through the media. This research is field research using interview, observation and documentation as data collection method. The expected outcome of this study is the offer of solutions to the character problem that occurs. Researchers are interested in doing research in boarding school Al-mumtaz because affective side is preferred and emphasized than cognitive even in the assessment and determination of class increases. The strategy undertaken in the internalization of Islamic character values based on the findings of researchers is a) through entrepreneur activities b) weekly moral value c) habituation d) reward and punishment e) exemplary from teacher f). surveillance and attitude setting for 24 hours.Â Keywords: values internalization, character building, Islamic boarding schoolÂ AbstrakKarakter adalah tindakan yang dilakukan tanpa pemikiran dan pertimbangan terlebih dahulu. Jadi orang yang berkarakter adalah orang yang melakukan dan merespon sesuatu dengan spontan dan reflek. Pembentukan karakter yang baik membutuhkan proses dan strategi yang tepat. Studi, kajian dan penelitian tentang karakter semakin penting dilakukan mengingat fenomena baru-baru ini terkait dengan kemunduran nilai dan karakter yang dilakukan oleh anak-anak yang masih tergolong kecil dan banyak tindakan lain yang menyimpang dari nilai-nilai karakter Islam, yang bisa kita lihat setiap hari melalui media. Penelitian ini merupakan penelitian lapangan dengan menggunakan wawancara, observasi dan dokumentasi sebagai metode pengumpulan data. Hasil yang diharapkan dari penelitian ini adalah tawaran solusi terhadap masalah karakter yang terjadi. Peneliti tertarik untuk melakukan penelitian di pesantren al-Mumtaz karena sisi afektif lebih diutamakan dan ditekankan daripada kognitif meski dalam penilaian dan penentuan kelas meningkat. Strategi yang dilakukan dalam internalisasi nilai karakter Islam berdasarkan temuan peneliti adalah a) melalui kegiatan wirausaha, b) nilai moral mingguan c) pembiasaan d) imbalan dan hukum e) contoh dari guru f) pengawasan dan penjagaan sikap selama 24 jam.Â Kata kunci: internalisasi nilai, pembangunan karakter, pondok pesantren